PSYCHIC RECOVERY AND MISSION OF IDENTITY OF WOMEN AS VICTIMS OF SEXUAL VIOLENCE - R. Iman Pribadi; Angga Wardana (UNES Law Review, 2023)
Psychological recovery and disguising the government's identity as a victim of sexual violence is a concrete problem. The government needs to provide support and protection for all existing legal mechanisms for victims of such violence. Although certain victims of sexual violence and harassment receive national media coverage, we must remember that the extent of the victims remains a secret. Too many victims remain afraid to come forward or lack confidence in complaints institutions. Based on this, preventing sexual assault and harassment from occurring must be of the utmost importance and for victims of previous incidents. This is to reduce the risk of the victim returning. recovery center, healing, their ability to rebuild their life and ongoing safety. Prevention is becoming more and more challenging. Many parents may find it difficult to talk to their children about the risks of sexual violence and abuse.